2018
DOI: 10.1111/mcn.12605
|View full text |Cite
|
Sign up to set email alerts
|

Peer counselling improves breastfeeding practices: A cluster randomized controlled trial in urban Bangladesh

Abstract: This study aimed to evaluate the impact of peer counselling on early initiation of breastfeeding (EIBF) and exclusive breastfeeding (EBF) rates for mother–infant pairs living in urban slums, Dhaka, Bangladesh. This randomized controlled trial enrolled 350 mother–infant pairs from selected slums between September 2014 and July 2016. The women assigned to intervention group received peer counselling from locally recruited, trained community female volunteers starting in third trimester of pregnancy until 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 42 publications
3
44
1
4
Order By: Relevance
“…Similar findings were reported from Ethiopia [36], Burkina Faso and Uganda [37]. In addition, evidence from Bangladesh and Tanzania revealed that breastfeeding counselling increases maternal knowledge on optimal infant feeding [38,39]. Mothers who are knowledgeable on IYCF are more likely to follow the WHO recommendations on practices such as early initiation of breastfeeding, EBF and avoidance of pre-lacteal feeds [40].…”
Section: Discussionmentioning
confidence: 54%
“…Similar findings were reported from Ethiopia [36], Burkina Faso and Uganda [37]. In addition, evidence from Bangladesh and Tanzania revealed that breastfeeding counselling increases maternal knowledge on optimal infant feeding [38,39]. Mothers who are knowledgeable on IYCF are more likely to follow the WHO recommendations on practices such as early initiation of breastfeeding, EBF and avoidance of pre-lacteal feeds [40].…”
Section: Discussionmentioning
confidence: 54%
“…This may be due to the nature of their advice. In the Muslim community, relatives or friends are the main people providing breastfeeding advice [30,38]. An intervention study conducted in urban Bangladesh has highlighted the need for community-based peer counseling using trained community female volunteers to promote good breastfeeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…An intervention study conducted in urban Bangladesh has highlighted the need for community-based peer counseling using trained community female volunteers to promote good breastfeeding practices. When peer counseling at home included other family members, mothers were five times more likely to practice exclusive breastfeeding for up to five months compared to mothers who received no intervention [38]. Peer counseling also had a positive effect on early initiation of breastfeeding within the first hour of birth [38].…”
Section: Discussionmentioning
confidence: 99%
“…Community-based IFAS education, including peer counselling which was positively implicated in a study in Bangladesh [47], yielded positive results in this study and needs further strengthening. Likewise, the importance of family support, especially husbands, in IFAS use is critical, just as indicated in a study in Zimbabwe [48].…”
Section: Discussionmentioning
confidence: 62%